2021
DOI: 10.1186/s12936-021-03705-2
|View full text |Cite
|
Sign up to set email alerts
|

Family, social and cultural determinants of long-lasting insecticidal net (LLIN) use in Madagascar: secondary analysis of three qualitative studies focused on children aged 5–15 years

Abstract: Background Although it is accepted that long-lasting insecticidal net (LLIN) use is an effective means to prevent malaria, children aged 5 to 15 years do not appear to be sufficiently protected in Madagascar; the malaria prevalence is highest in this age group. The purpose of this research is to summarize recent qualitative studies describing LLIN use among the Malagasy people with a focus on children aged 5–15 years. Methods Qualitative data from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…While malaria affects both males and females [ 34 , 35 ], gender was identified as a factor that influenced the vulnerability to malaria infection. The present study showed that males were significantly more likely to harbour a P. falciparum infection than female subjects, which could be the result of differences in exposure patterns between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…While malaria affects both males and females [ 34 , 35 ], gender was identified as a factor that influenced the vulnerability to malaria infection. The present study showed that males were significantly more likely to harbour a P. falciparum infection than female subjects, which could be the result of differences in exposure patterns between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these results are not different from other African studies [19], but specifically, the frequency of daily compliance to LLINs may vary for innumerable reasons between different populations and is most likely context specific. For instance, some African studies show stigmatizing (e.g., bednet as dead body cover) and practical (e.g., inadequate bednet for entire household) patterns related to bednet use [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the local ecologies of each cluster will likely alter the potential for transmission given ratios of mosquitoes to people associated with rainfall, temperature, and land-use [51][52][53] , the preference of local mosquitoes to bite during the night, on people or indoors [54][55][56][57] . The use of nets over seasons may well cycle with peaks in net use occurring when the risk of transmission is greatest 58 , and net use may also vary among community members of different ages 59 . Coupled with these socioecological reasons, the addition and use of complementary interventions has altered over time which is likely to contribute further to variability in these DHS data.…”
Section: Discussionmentioning
confidence: 99%